Effects of nnav1.5 expression modulation on mhc I antigen processing machinery and invasion potential of breast cancer cells - Din, Ahmad Hafiz Murtadha Noor (2024)
The increase in expression and activity of voltage-gated sodium channel’s (VGSC) isoform, neonatal Nav1.5 (nNav1.5) in breast cancer have been associated with enhanced metastatic ability. Loss of immune surveillance enables cancer cells to metastasize hence this study is to explore the possible role of nNav1.5 in regulating the expression of immune components, MHC I antigen processing machinery (APM), which is deregulated in breast cancer. Several reports link VGSC and APM in neurons, but the correlation between nNav1.5 and APM in breast cancer is unknown. In this study, the gene expression of APM components (PSMB8, PSMB9, PSMB10, TAP1, TAP2, B2M and MHC I) and CD274 were measured and compared in the highly aggressive MDA-MB-231, less aggressive MCF-7 and control, non-cancerous breast epithelial, MCF 10A via real-time PCR. Gene expression of nNav1.5 and two metastatic markers, MMP1 and FN1, were included. After 3D spheroids for MDA-MB-231 and MCF-7 were established via liquid overlay method, their target genes’ expression was compared with the monolayer counterparts. The spheroid volumes were analysed using SpheroidSizer. To block nNav1.5 expression, tetrodotoxin (TTX) and siRNA were employed in MDA-MB-231 monolayer and spheroids, while Trichostatin A and nNav1.5-plasmid were utilised to increase nNav1.5 expression in MCF-7 monolayer and spheroids. The effects of modulating nNav1.5 were assessed by profiling all target genes using real-time PCR and on spheroid invasion ability using Cultrex kit. In monolayer model, highest nNav1.5 gene level was detected in MDA-MB-231 > MCF-7 but absent in MCF 10A. In contrast, MHC I, B2M, PSMB8, PSMB9, TAP1 and TAP2 were at the highest level in MCF 10A > MDA-MB-231 > MCF-7, except for PSMB10 with MCF-7 > MDA-MB-231. For CD274, the highest level was in MDA-MB-231 > MCF 10A > MCF-7. In spheroids of MDA-MB-231 and MCF-7, the level of nNav1.5, MMP1, and FN1, were upregulated but there were no changes in almost all APM genes (except TAP1 downregulation), compared to their respective monolayer model. CD274 is downregulated in MDA-MB-231 spheroid but upregulated in MCF-7 spheroid, compared to their monolayer model. In nNav1.5 blocking monolayer experiments, TTX upregulated nNav1.5, TAP2, B2M, MMP1, and FN1 but downregulated PSMB9. Alternatively, siRNA knocked down nNav1.5 gene (73.22% after 48 hours, 10 nM siRNA) in MDA-MB-231, thus resulted in the upregulation of B2M and MHC I, and the downregulation of PSMB8, PSMB9, PSMB10, TAP2, and CD274, but unchanged MMP1 and FN1. However, in MDA-MB-231 spheroid, both TTX and siRNA failed to induce expressional changes. On the invasion ability, siRNA pre-treated spheroid failed to form. In MCF-7 monolayer and spheroid model, TSA induced nNav1.5, PSMB9, B2M, MHC I, CD274, and MMP1 expression. In monolayer MCF-7, nNav1.5 upregulation via plasmid transfection increased all target genes but in spheroid, only nNav1.5 and MHC I were upregulated, while PSMB10 and B2M were downregulated. TSA showed increased spheroid invasion, but nNav1.5-plasmid pre-transfected cells formed spheroids with lower relative perimeter diameter. In summary, modulating nNav1.5 gene expression affected MHC I APM, CD274, and cell behaviour, hence can potentially improve breast cancer immunotherapies by countering tumour immune escape mechanism via rescuing MHC I. Overall, the study’s current findings support the influence of nNav1.5 on the expression regulation of immune component molecules in breast cancer.